1990
DOI: 10.1128/jcm.28.11.2448-2455.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mice and moles inhabiting mountainous areas of Shimane Peninsula as sources of infection with Yersinia pseudotuberculosis

Abstract: A total of 1,835 Yersinia spp. were isolated from 925 (60.5%) of 1,530 wild mice and from 139 (79.9%) of 174 moles living in mountainous areas of eastern Shimane Prefecture, Japan. The Yersinia spp. included 1,106 Yersinia enterocolitica, 26 Y. enterocolitica-like, 176 Yersinia mollaretii, 149 Yersinia frederiksenii, 70 Yersinia intermedia, 231 Yersinia kristensenii, 5 Yersinia aldovae, and 72 Yersinia pseudotuberculosis. Human pathogenic Y. enterocolitica was not isolated. Y. pseudotuberculosis was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…Eighteen species of rodents were represented: the majority of Y. enterocolitica and Y. enterocolitica-like strains isolated from rodents in rural areas were from Microtus nivalis and Microtus socialis, while strains isolated from rodents in urban areas were generally cultured from Rattus norvegicus. These data are compatible with the hypothesis that rodents are a reservoir for Y. enterocolitica and Y. enterocolitica-like strains; similar findings have been reported from Japan by Fukushima et al (4) and Kaneko and Hashimoto (5).…”
supporting
confidence: 92%
“…Eighteen species of rodents were represented: the majority of Y. enterocolitica and Y. enterocolitica-like strains isolated from rodents in rural areas were from Microtus nivalis and Microtus socialis, while strains isolated from rodents in urban areas were generally cultured from Rattus norvegicus. These data are compatible with the hypothesis that rodents are a reservoir for Y. enterocolitica and Y. enterocolitica-like strains; similar findings have been reported from Japan by Fukushima et al (4) and Kaneko and Hashimoto (5).…”
supporting
confidence: 92%
“…Isolation and identification of Yersinia spp. The organs (liver, spleen, lung, small intestine, and intestinal content) of the dead monkeys were homogenized in phosphate-buffered saline (PBS; pH 7.2) and 10-fold serial dilutions of the suspension were plated on irgasan-novobiocin (IN) agar plates (10). All PBS suspensions were incubated at 4 C for 3 weeks as a cold enrichment.…”
mentioning
confidence: 99%
“…The infectivity and pathogenicity of Y. enterocolitica 0 : 8 to A . speciosus appears to be basically the same as that of Y. pseudotuberculosis, which has occasionally been isolated from wild rodents (KANEKO and HASHIMOTO, 1981;FUKUSHIMA et al, 1990), but not the same as that of Y. enterocolitica 0:3. The isolation of Y. enterocolitica 0:8 from A .…”
Section: Discussionmentioning
confidence: 71%
“…Although a few reports of the isolation of serovar 0 :3 biovar 4 from house rats associated with swine have been published (ALDOVA et al, 1977;KANEKO et al, 1978), virulent Y. enterocoliticu, such as serovars 0 : 3 biovar 4, 0 : 5B biovar 2, 0 : 8 biovar 1, and 0:9 biovar 2, have not been frequently isolated from wild rodents (KANEKO and US. Copyright Clearance Center Code Statement: 0931 -1793/94/4107-0504$10.50/0 HASHIMOTO, 1981;FUKUSHIMA et al, 1990). In addition, it was shown that Mus musculus mice infected orally with Y. enterocoliticu 0 : 8 develop fatal septicemia (CARTER, 1975).…”
Section: Introductionmentioning
confidence: 99%